The crossover - Alexander, Kwame (Boston : Houghton Mifflin Harcourt, 2014)
Fourteen-year-old twin basketball stars Josh and Jordan wrestle with highs and lows on and off the court as their father ignores his declining health.
Bulletin of the Center for Children's Books starre
Library Media Connection starred
School Library Journal starred
Booklist, March 2014
Bulletin of the Center for Children's Books starre, February 2014
Horn Book, May 2014
Keywords: African Americans -- Juvenile fiction; Brothers -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Twins -- Juvenile fiction; African Americans -- Fiction; Basketball -- Fiction; Brothers -- Fiction; Fathers and sons -- Fiction; Novels in verse; Twins -- Fiction; African Americans -- Fiction; Basketball -- Fiction; Brothers -- Fiction; Father-son relationship -- Fiction; Novels in verse; Twins -- Fiction; Basketball stories; Novels in verse